2017
DOI: 10.1177/1081286517736999
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of thermoelastic waves across an interface with consideration of couple stress and second sound

Abstract: The reflection and transmission of thermoelastic waves across an interface between two different couple stress solids are studied based on the thermoelastic Green–Naghdi theory with consideration of second sound. First, some thermodynamic equations of a couple stress elastic solid are formulated and the function of free energy density is postulated. Second, equations of thermal motion and heat conduction of the couple stress elasticity are derived and constitutive relations with thermoelastic coupled effects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 30 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…It is found that for a two-dimensional model, there exist four coupled longitudinal waves, that is, longitudinal displacement wave, thermal wave, mass diffusion wave and longitudinal microstretch wave, as well as two coupled transverse waves. Considering the strain gradient theory and coupled stress theory, Li et al [45][46][47][48] further derived the governing equations of thermoelastic waves corresponding to the L-S, G-L and G-N generalized thermoelastic theories, and studied the dispersion and attenuation characteristics of thermoelastic waves, as well as the characteristics of reflection and transmission. It was found that the thermo-mechanical coupling effect only affects the longitudinal wave, not the shear wave.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that for a two-dimensional model, there exist four coupled longitudinal waves, that is, longitudinal displacement wave, thermal wave, mass diffusion wave and longitudinal microstretch wave, as well as two coupled transverse waves. Considering the strain gradient theory and coupled stress theory, Li et al [45][46][47][48] further derived the governing equations of thermoelastic waves corresponding to the L-S, G-L and G-N generalized thermoelastic theories, and studied the dispersion and attenuation characteristics of thermoelastic waves, as well as the characteristics of reflection and transmission. It was found that the thermo-mechanical coupling effect only affects the longitudinal wave, not the shear wave.…”
Section: Introductionmentioning
confidence: 99%
“…Biswas and Sarkar [32] found a solution of the oscillations equations in porous thermoelastic medium. Li et al [33] have examined the effects of couple stress on the propagation of thermoelastic waves. Saha et al [34] showed the effects of initial stresses and gravity field on the reflection and refraction coefficients of plane waves.…”
Section: Introductionmentioning
confidence: 99%
“…The reflection of longitudinal waves in non-dissipative medium including the effect of rotation was discussed by Sing et al [19]. More recently, Biswas and Sarkar [20] derived the solution of the steady oscillations equations in porous thermos-elastic medium and Li et al [21] discussed the propagation of thermos-elastic waves across an interface with consideration of couple stress and second sound on the basis of Green and Naghdi GN theories. Saha et al [22] analyzed the reflection and refraction of plane wave at the separating interface of two functionally graded incompressible monoclinic media under initial stress and gravity.…”
Section: Introductionmentioning
confidence: 99%